Ginseng intake and Alzheimer disease-specific cognition in older adults according to apolipoprotein ε4 allele status - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Choi, Ihn-Geun; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Jhoo, Jin Hyeong; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2023)
Background: The probable association among ginseng intake, Alzheimer’s disease (AD)-specific cognition, and apolipoprotein ε4 (APOE4) remains poorly investigated. Hence, we examined the association between ginseng intake and AD-specific cognition in older adults under the moderating effect of APOE4 status. Methods: This study enrolled 160 adults aged 65-90 years without dementia. All participants underwent comprehensive dietary and clinical assessments including ginseng intake, AD-related cognition (i.e., delayed episodic memory, as the earliest cognitive change in AD), and non-memory cognition for comparative purposes. Results: Ginseng intake was associated with higher delayed episodic memory, but not non-memory cognition, compared to no ginseng intake. The interaction between ginseng intake and APOE4 status had a significant effect on delayed episodic memory. Subgroup analyses showed that ginseng intake was associated with higher delayed episodic memory in the APOE4-negative but not the APOE4-positive subgroup. The benefits of ginseng intake on delayed episodic memory were prominent in the high duration (≥ 5 years) and midlife onset (< 65 years) groups. Conclusions: Our study of older adults with no dementia suggests that ginseng intake (with high duration and midlife onset) had a beneficial effect on AD-specific cognitive decline, i.e., the delayed episodic memory. In addition, APOE4 status moderates the association between ginseng intake status and AD-specific cognitive decline.